An incidental finding of a gastrointestinal stromal tumor (GIST) in the stomach following laparotomy: Case report and literature review (2014)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract. The annual frequency of this pathology in developed countries is estimated to be between 6.5 and 14.5 cases per million people. Most GISTs (50-70%) originate in the stomach. Symptoms vary from nonspecific abdominal complaints to abdominal pain with or without a palpable abdominal mass. Some of these patients are diagnosed incidentally when they undergo screening or upper endoscopy to diagnose bleeding. We present a case of GIST which was initially discovered because of upper gastrointestinal bleeding during a laparoscopic cholecystectomy. © 2014 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.